A translational approach to the renin-angiotensin-aldosterone system in heart failure - Bakogiannis, Constantinos; Theofilogiannakos, Efstratios; Papadopoulos, Christodoulos; Lazaridis, Charalampos; Bikakis, Iosif; Tzikas, Stergios; Vassilikos, Vassilios (Annals of Research Hospitals, 2019)
The renin-angiotensin-aldosterone system (RAAS) is a well-studied neurohormonal cascade that plays key role in various homeostatic mechanisms, such as blood pressure control and tissue perfusion balance. Dysregulation of RAAS has been involved in the pathogenesis of various cardiovascular disorders. Heart failure (HF) is a very common cardiovascular disease with significant morbidity and mortality. RAAS participates in the pathogenesis of HF and it has been indicated as important therapeutic target. Angiotensin-converting enzyme inhibitors (ACEi), angiotensin receptor blockers (ARBs) and mineralocorticoid receptor antagonists (MRAs) and recently angiotensin receptor-neprilysin inhibitors (ARNIs) are the most common used RAAS-modifying therapies that significantly improved the mortality and the morbidity of patients with HF and reduced ejection fraction. On the other hand, the aforementioned therapeutic choices failed to show promising results in HF with preserved ejection fraction. This article discusses current knowledge on the role of RAAS modulation in HF and our therapeutic options.